Sein und Teilen: Eine Praxis schöpferischer Existenz - Weber, Andreas (transcript, 2017)
In order to develop a different economy and a sustainable relationship with nature and ourselves, we need to abandon our false perceptions of reality. We believe in the idea of death and separation, the distribution of inanimate resources, and the consumption space of private, psychological affairs. Our reality, however, is characterised by vitality. This is a commons – a passionate relational process, in which identity is always realised through others and as a function of the whole. Our metabolism, meaningful relationships and sensory experiences, as well as the exchange of goods and services, can only prosper if we conceive of them as a common participation in a creative reality.